LATERAL SURVIVAL: AN OT ACCOUNT - Yip, Moira (International Journal of English Studies, 2009)
When laterals are the targets of phonological processes, laterality may or may not survive. In a fixed feature geometry, [lateral] should be lost if its superordinate node is eliminated by either the spreading of a neighbouring node, or by coda neutralization. So if [lateral] is under Coronal (Blevins 1994), it should be lost under Place assimilation, and if [lateral] is under Sonorant Voicing (Rice & Avery 1991) it should be lost by rules that spread voicing. Yet in some languages lateral survives such spreading intact. Facts like these argue against a universal attachment of [lateral] under either Coronal or Sonorant Voicing, and in favour of an account in terms of markedness constraints on feature-co-occurrence (Padgett 2000). The core of an OT account is that IFIDENTLAT is ranked above whatever causes neutralization, such as SHARE-F or *CODAF. laterality will survive. If these rankings are reversed, we derive languages in which laterality is lost. The other significant factor is markedness. High-ranked feature co-occurrence constraints like *LATDORSAL can block spreading from affecting laterals at all.